2021
DOI: 10.1029/2020jd034214
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Online and Offline Data Assimilation Comparison for Paleoclimate Reconstruction: An Idealized OSSE Study

Abstract: Knowledge of past climate conditions is crucial to understanding the climate system. Recently, data assimilation (DA) has been applied to reconstruct paleoclimate of the last millennium (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
(135 reference statements)
0
12
0
Order By: Relevance
“…The default ensemble size is 100, which is consistent with that in Hakim et al (2016). The Covariance localization is used to localize the impact of observations and mitigate spurious error correlations between observations and state variables resulted from a limited ensemble size (e.g., Okazaki et al, 2021;Valler et al, 2019). The Gaspari and Cohn (GC; Gaspari & Cohn, 1999) function that is a fifth-order piecewise polynomial function is used for localization.…”
Section: Experimental Designmentioning
confidence: 99%
“…The default ensemble size is 100, which is consistent with that in Hakim et al (2016). The Covariance localization is used to localize the impact of observations and mitigate spurious error correlations between observations and state variables resulted from a limited ensemble size (e.g., Okazaki et al, 2021;Valler et al, 2019). The Gaspari and Cohn (GC; Gaspari & Cohn, 1999) function that is a fifth-order piecewise polynomial function is used for localization.…”
Section: Experimental Designmentioning
confidence: 99%
“…Second, advances in data assimilation now allow paleoclimate data to be assimilated into paleoclimate simulations (Tierney et al 2020;Okazaki et al 2021). The use of isotopic records in data assimilation is made more powerful by advances in proxy system forward-modeling approaches (Okazaki and Yoshimura 2019) and by the recent development of isotopic data compilations (e.g., Comas-Bru et al 2020).…”
Section: Showcases Of Water Isotopes In Specific Research Topicsmentioning
confidence: 99%
“…Based on an intermediate complexity general circulation model, Okazaki et al. (2021) showed that the online PDA could outperform the offline PDA when the length of predictability is longer than the averaging time of observations, and the ocean plays an important role to extend predictability that is helpful for online PDA. Although online PDA is feasible with a simplified model or a linear inverse model (e.g., Jebri & Khodri, 2023; Perkins & Hakim, 2017), online PDA could require intensive computational cost for the paleoclimate simulations with a realistic and complex model, due to the length of simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a linear inverse model of coupled atmosphere-ocean dynamics was applied for online PDA, and the reconstructed annual-resolution atmosphere and ocean fields demonstrated the added value of dynamical memory for the proxy data and physical constraints from the atmosphere-ocean interaction (Perkins & Hakim, 2021). Based on an intermediate complexity general circulation model, Okazaki et al (2021) showed that the online PDA could outperform the offline PDA when the length of predictability is longer than the averaging time of observations, and the ocean plays an important role to extend predictability that is helpful for online PDA. Although online PDA is feasible with a simplified model or a linear inverse model (e.g., Jebri & Khodri, 2023;Perkins & Hakim, 2017), online PDA could require intensive computational cost for the paleoclimate simulations with a realistic and complex model, due to the length of simulations.…”
mentioning
confidence: 99%